The Effect of Emotional Intelligence and Self-Efficacy on the Sense of Dark Humor in Students of the Faculty of Psychology - Abdul Wahid Zaini; Ayatullah Maulidi (Journal of Psychological Insight, 2025)
This study examines the impact of emotional quotient (EQ) and self-efficacy on the perception of dark humor among psychology students. Dark humor, which involves satirical or morbid themes, is linked to cognitive and emotional processes, making it relevant to psychological research. EQ refers to an individual’s ability to perceive, understand, and regulate emotions, while self-efficacy is the belief in one’s capability to overcome challenges. Using a quantitative correlational design, this research employed purposive sampling to select psychology students. Standardized scales measured EQ, self-efficacy, and dark humor appreciation, while multiple regression analysis assessed their impact on humor tendencies. The findings suggest that both EQ and self-efficacy significantly shape students’ humor preferences. Higher EQ is associated with a deeper understanding and appropriate use of dark humor, while self-efficacy boosts confidence in expressing it socially. These results underline the role of psychological factors in humor appreciation and highlight the importance of emotional regulation and self-confidence in humor expression.